Exploration of numerical tafsir ideas on Nadirsyah Hosen's social media - Nuzuliyah, Wilda Rahmatin; Fitri, Annisa (C-DISC, 2023)
Social media, usually used as a medium to communicate with each other, has been transformed into a means/container to express Gus Nadir's ideas about the Qur'an and tafsir. This paper aims to examine Gus Nadir's ideas about numerical tafsir, which deviate from his concern about arbitrary interpretations and tend to be mere matchology on social media. An in-depth analysis of his work entitled